Effect of an interprofessional small-group communication skills training incorporating critical incident approaches in an acute care and rehabilitation clinic specialized for spinal cord injury and disorder - Anke Scheel-Sailer; Anke Scheel-Sailer; Stephanie Eich; Luca Jelmoni; Patricia Lampart; Patricia Lampart; Michael Schwitter; Diana Sigrist-Nix; Diana Sigrist-Nix; Wolf Langewitz (Frontiers Media S.A., 2022)
AimTo investigate the impact of site-specific inter-professional small-group communication skills training (CST) that incorporates critical incident approaches to learning on patient satisfaction with communication.SettingRehabilitation clinic specialized for spinal cord injury/disorder (SCI/D).MethodsRetrospective observational cohort study design using patient and health-professional self-report data. Data for patient satisfaction with communication were collected in 2014 (existing records) and each year from 2015 to 2021 (post-program; volunteers) using the MECON survey.ResultsFifteen basic (n = 161 participants), 16 refresher (n = 84), and five short (n = 17) CST seminars were conducted. Overall, 262 employees (105 physicians, 63 nurses, 36 physio- and occupational therapists, and 58 others) participated; 92 participants (response rate 37.6%) responded to feedback surveys. They rated the seminars positive concerning the alternation between theory, discussion, and practical exercise in 91.3%, and rated the length of the training ideal in 80.2%. Post-program patient satisfaction overall increased from 83.1% (confidence interval (CI) 2.6%) to 90% (CI 0.8%; R2 = 0.776; p= 0.004). It was higher in specific communication-related topics: "receiving information" (81.1%, CI 3.1-90.2%, CI 1.0%; p = 0.003), "being able to bring in concerns" (83%, CI 1.0-90.8%; R2 = 0.707; p = 0.009) and "being treated with respect" (89.4%, CI 2.6-94.4%, CI 0.8%; R2 = 0.708; p = 0.004).Practice implicationsInter-professional CST is feasible and well accepted by professionals from various professional groups. During seven years of continuous training, independent patient ratings of satisfaction with professional communication have improved significantly. Participants attest to the training's high credibility and usefulness in everyday life.